Biologging subcutaneous temperatures to detect orientation to solar radiation remotely in savanna antelope. Issue 5 (29th April 2019) - Botha, Arista; Lease, Hilary M.; Fuller, Andrea; Mitchell, Duncan; Hetem, Robyn S.
Abstract: Observations of animal thermoregulatory behavior are labor‐intensive, and human presence may disturb the normal behavior of the animal. Therefore, we investigated whether a remote biologging technique could be used to detect orientation to solar radiation in savanna antelope. We predicted that when a mammal was orientated perpendicular to solar radiation, the subcutaneous temperature on the side of the body facing the sun would be greater than that on the opposite side, whereas when the mammal was orientated parallel to solar radiation, subcutaneous temperatures on both sides would be similar. A pilot study showed that the difference between left‐ and right‐side temperatures under a pelt reflected orientation to solar radiation if a pelt‐covered cylinder had been orientated for 15 min or longer. In addition, the rate of change in temperature difference could detect orientation that had changed within the previous 5 min. We implanted temperature‐sensitive data loggers subcutaneously into the flanks of eight black ( Connochaetes gnu ) and eight blue ( Connochaetes taurinus ) wildebeest. By incorporating both the rate of change and subcutaneous temperature differences and excluding times when wildebeest were lying down, our predictions correctly matched behavioral observations of wildebeest orientation to solar radiation 71% of the time. Our technique tended to fail when wildebeest were lying down, wind speeds were high and the sun was overhead. But those are conditions in which the benefits of manipulating orientation to solar radiation is of diminishing importance to a free‐living mammal. Therefore, subcutaneous temperatures provide physiologically relevant information on the importance of solar radiation to mammals. Abstract : We hypothesized that when an antelope was orientated perpendicular to solar radiation, the side of the antelope's body facing the sun would heat up more than the opposite side, whereas when the antelope was orientated parallel to solar radiation, subcutaneous temperatures on both sides of the body would be similar. HIGHLIGHTS: Subcutaneous temperature measured remotely by biologgers could be used to identify orientation to solar radiation of free‐living wildebeest correctly 71% of the time and to quantify heat gain during orientation behaviors.